The bactericidal activity of sera of healthy neonates and of newborns with hyperbilirubinaemia to Escherichia coli - Miler, I; Vondrácek, J; Hromádková, L (Folia microbiologica, 1979)
Cord and newborn sera were found to possess a significantly decreased in vitro bactericidal activity to Escherichia coli as compared to sera of adult individuals. Hyperbilirubinaemia in neonates suffering from both Rh and ABO incompatibility results in a further significant impairment of the bactericidal activity of their sera in comparison with healthy newborn infants. Exchange transfusion improved considerably the serum bactericidal activity. The possible mechanism of toxic action of unconjugated bilirubin on cells of the immune system is discussed.
Keywords: Middle Aged; mužské pohlaví; Fetal Blood; Adult; Infant, Newborn; ženské pohlaví; Escherichia coli; novorozenec; Humans; Blood Transfusion; Jaundice, Neonatal; lidé středního věku; novorozenecká žloutenka; krevní transfuze; baktericidní aktivita krve; Blood Bactericidal Activity; dospělí; Female; fetální krev; lidé; Male